A STATISTICAL POWER ANALYSIS OF ANALES DE PSICOLOGÍA - Sánchez Meca, Julio; Valera Espín, Antonio; Velandrino Nicolás, Antoino P.; Marín Martínez, Fulgencio (Anales de Psicología / Annals of Psychology)
The aim of this paper was to determine the statistical power of the research published in the journal Anales de Psicología across its life (1984-1991). The sixteen studies avalaible for this calculation were used for analyzing their statistical power. The results do not seem to differ form those originally obtained by Cohen (1962), showing average powers of .13, .47, and .76 for small, medium, and large effect sizes, respectively. Also, the mean power for the estimated Finally, the results are compared to other recent power studies.